Estrategia didáctica "JUDIPI" (Juego, Dibujo y Pintura), para mejorar el Nivel de Aprendizaje de la escritura en los alumnos de primer grado de nivel primaria de la Institución Educativa Experimental José Carlos Mariátegui "Centro de Aplicación de la FEH-R'' del sector Rupacucha, distrito de Rioja. - Correa Mozo, Cinthia Yvonne (2008)
Show it(subj) investigation has had as general objective to apply the didactic strategy JUDIPI to lift the learning first-degree level of the writing in the lnstitution Educativa Experimental José Carlos Mariátegui FEH'S pupils - the sector's R Rupacucha, with the one and only to be able to than the boys and girls purpose Let them write or Let them produce texts expressing his needs and interests according to his level of development. study has as support the pedagogic methodology's underlying principles: Pedagogic, sociological, psychological, epistemológico and philosophical, based in these beginnings, they formulated themselves them hypothesis: Alternative Hypothesis: lf JUDIPI applies didactic strategy himself, then rises significantly the learning first degree level of the writing in the pupils of the sector's lnstitution Educativa Experimental .José Carlos Mariátegui Rupacucha, FEH - Rioja. Void Hypothesis: lf JUDIPI applies didactic strategy himself, then does not rise the learning first-degree level of the writing in the pupils of the sector's lnstitution Educativa Experimental José Carlos Mariátegui Rupacucha, FEH - Rioja. The study Sign was shaped for eigtheen pupils: Nine women and nine males, whom he named him group of people of study. In order to them contrastation hypothesis experimental pre with pre utilized the act-finding design himself and behind test with an alone group. To the study group applied it a pre test to determine the learning level to the stimulus's, applicatioi1 ( didactic strategy JUDIPI ), next previous developed him 19 sessions learning in the one that the didactic strategy put into practice itself JUDIPI, as stímulus to raise wríting's learning. Right after making contrast them hypothesis, tabulating of data, and after the analysis and respective interpretation, JUDIPI demonstrated himself than the didactic strategy C raised the learning of the level's writing.